1990
DOI: 10.1073/pnas.87.19.7633
|View full text |Cite
|
Sign up to set email alerts
|

Wound-induced accumulation of mRNA containing a hevein sequence in laticifers of rubber tree (Hevea brasiliensis).

Abstract: Hevein is a chitin-binding protein that is present in laticifers of the rubber tree (Hevea brasilensis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
152
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(160 citation statements)
references
References 33 publications
6
152
0
2
Order By: Relevance
“…It is identical to residues 159-173 corresponding to the cDNA sequence of the hevein precursor [4], except for the two underlined residues, which are Ile and Asp, respectively, in the latter. We do not know the cause of these differences.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…It is identical to residues 159-173 corresponding to the cDNA sequence of the hevein precursor [4], except for the two underlined residues, which are Ile and Asp, respectively, in the latter. We do not know the cause of these differences.…”
Section: Resultsmentioning
confidence: 90%
“…Broekaert et al [4] have determined its cDNA sequence and found that it is synthesized as a precursor with a signal sequence of 17 residues, followed by the hevein domain of 43 residues and a C-terminal region of 144 residues. The C-terminal domain and the precursor consisting of the hevein and the C-terminal domain are also present in the lutoid-body fraction of latex [5].…”
Section: Introductionmentioning
confidence: 99%
“…The sequence is very similar to that of the protein hevein (isolated from rubber tree latex) which folds into a 'toxin-agglutinin fold' or 'hevein domain' [2]. Structure determination of hevein by ~H NMR [3] and of WGA by X-ray diffraction [4] have shown that the WGA domains and hevein have a common structural fold.…”
Section: Introductionmentioning
confidence: 73%
“…Among them, the hevein-like peptides, such as hevein from laticifers of rubber tree (4,5), antimicrobial peptides from Amaranthus caudatus seeds (Ac-AMP) (6,7), and antifungal peptides from the seeds of Pharbitis nil (Pn-AMP) (8), have specific chitin-binding activities and are characterized by three or four disulfides to stabilize a chitin-binding domain referred as hevein domain (2,9) as shown in Figure 1. This hevein domain mostly consists of 30-43 residues including six or eight cysteines pairing into three or four disulfide bonds, three aromatic residues, two glycines, and one serine ( Figure 1) and occurs in a variety of plant proteins and peptides in multiple or single copies, respectively (2).…”
mentioning
confidence: 99%